Emerging Insights into Stevens-Johnson Syndrome and Toxic Epidermal Necrolysis Induced by Immune Checkpoint Inhibitor and Tumor-Targeted Therapy - Lin M; Gong T; Ruan S; Lv X; Chen R; Su X; Cheng B; Ji C (Dove Medical Press, 2024)
Min Lin,1,* Ting Gong,2,* Shifan Ruan,1,* Xiaoqing Lv,1 Rongying Chen,1 Xinhong Su,1 Bo Cheng,1 Chao Ji1 1Department of Dermatology, The First Affiliated Hospital of Fujian Medical University, Fuzhou, 350000, People's Republic of China; 2Department of Central Laboratory, The First Affiliated Hospital of Fujian Medical University, Fuzhou, 350000, People's Republic of China*These authors contributed equally to this workCorrespondence: Bo Cheng; Chao Ji, Department of Dermatology, The First Affiliated Hospital of Fujian Medical University, 20 Chazhong Road, Taijiang District, Fuzhou, 350000, People's Republic of China, Tel +86 13859024296 ; +86 18651619908, Email bochengg@163.com; jichaofy@fjmu.edu.cnObjective: Anticancer drugs have revolutionized tumor therapy, with cutaneous toxicities such as Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) being common immune-related adverse events. The debate over the efficacy of systemic corticosteroids in treating these conditions persists, while tumor necrosis factor (TNF)-alpha inhibitors show promise. This study aims to evaluate the effectiveness and safety of combination therapy involving the TNF-α inhibitor adalimumab for SJS/TEN induced by anticancer drugs.Methods: A literature review of SJS/TEN cases induced by anticancer drugs from 1992 to 2023 was conducted, alongside an analysis of patients admitted to the First Affiliated Hospital of Fujian Medical University during the same period. Clinical characteristics, skin healing time, mortality, and adverse events were evaluated in two treatment groups: SJS/TEN patients treated with targeted anticancer therapies and immunotherapies.Results: Among the 27 patients studied (18 with SJS or SJS-TEN overlapping and 9 with TEN), combination therapy with adalimumab significantly reduced mucocutaneous reepithelization time and healing duration compared to corticosteroid monotherapy. Patients receiving adalimumab combined with corticosteroids had lower actual mortality rates than those on corticosteroid monotherapy. The combination therapy also showed a trend towards reducing standardized mortality rates based on the Score of Toxic Epidermal Necrolysis (SCORTEN).Conclusion: The findings suggest that adalimumab in combination with corticosteroids provides significant clinical benefits and is safer than corticosteroids alone for treating SJS/TEN induced by targeted anticancer therapies and immunotherapies. This study contributes valuable insights into potential treatment strategies for severe cutaneous adverse reactions to anticancer drugs, highlighting the importance of exploring alternative therapies such as TNF-α inhibitors in managing these conditions effectively.Keywords: anti-TNF-α, adalimumab, treatment, Stevens-Johnson syndrome, toxic epidermal necrolysis